Answer:
C.
Explanation:
In trigonometry, we have an equation as following:
![sine^(2) x + cosine^(2) x = 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/m847n86htazlbrp38d4k9z9ajh2fodkw45.png)
Replace θ into the above equation, we would have:
(sine θ)^2 + (cosine θ)^2 = 1
=> (sine θ)^2 = 1 - (cosine θ)^2 (1)
As given, we have cosine θ = -3/7. Replace it into the equation (1), we have:
(sine θ)^2 = 1 - (-3/7)^2
=>(sine θ)^2 = 1 - 9/49 = 40/49
=> sine θ = ±
= ±
![(2√(10) )/(7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/3y62g7t77ecwsvvzz3atifsa111pe7smci.png)
So sine θ =
or sine θ = -
However, as θ is in quadrant II, sine θ has a positive value
=> sine θ =
So that the correct answer is C